CLIL (CONTENT AND LANGUAGE INTEGRATION LEARNING) KASBIY KOMMUNIKATSIYA SOHASIDA IKKI TILLILIK, PEDAGOGIK MAHORAT, BILIM VA KO’NIKMALAR - Norquziyeva, Z.K. (SCIENCE and SOCIETY, 2021)
The article describes the technology of bilingual education, the formation, mastering and the order of teaching. Bilingualism and its consequences and what it gives us. Information was given about the functions of education and methods of formation, pedagogical skills and its technology.